Retrospective Comparison of 27-Gauge and 25-Gauge Microincision Vitrectomy Surgery with Silicone Oil for the Treatment of Primary Rhegmatogenous Retinal Detachment - Jie Li; Bo Zhao; Sanmei Liu; Fang Li; Wentao Dong; Jie Zhong (Journal of Ophthalmology)
Aim. To retrospectively compare the safety and effectiveness of 27-gauge (27G) microincision vitrectomy surgery (MIVS) with 25-guage (25G) MIVS for the treatment of primary rhegmatogenous retinal detachment (RRD) with silicone oil tamponade. Methods. Ninety-two patients with RRD who underwent MIVS from May 1, 2015, to June 30, 2017, were included in this study. Fifty-eight eyes underwent 25G MIVS and 34 eyes underwent 27G MIVS. We analyzed the characteristics of the patients, surgical time, main clinical outcomes, and rate of complications. Results. The mean surgical time was 56.7 ± 35.9 min for the 25G MIVS and 55.7 ± 36.1 min for the 27G MIVS, and there was no significant difference (P=0.894) between the two groups. The primary anatomical success rate after a single operation was 94.8% for 25G MIVS and 91.2% for 27G MIVS (P=0.666). Baseline and final visit best-corrected visual acuity (BCVA) were 1.9 ± 1.1 and 1.0 ± 0.8 in the 25G group, and 1.7 ± 1.0 and 1.1 ± 0.8 in the 27G group. Last visit BCVA increased significantly in both groups (P<0.001). However, there were no significant differences in terms of visual improvement ratio (>0.2 logMAR) between the two groups (P=0.173). No severe intraoperative complication was observed. Iatrogenic retinal breaks occurred in 2 eyes (3.4%) in the 25G group and 1 eye (2.9%) in the 27G group during the peripheral vitreous base shaving. The transient ocular hypertension (>25 mmHg) within postoperative week 1 was 25.9% in the 25G group and 11.8% in the 27G group (P=0.120). Conclusions. This study found no significant anatomical or functional difference between 27G and 25G MIVS in the treatment of primary RRD. Therefore, 27G vitrectomy appears to be a safe and effective surgery for the treatment of primary RRD.